Pengembangan Media Pembelajaran E-Modul dengan Flip PDF Professional Berbasis QR Code pada Mata Pelajaran Fiqih di MTsN 5 Jombang - Neny Liftia; Khoirun Nisa' (YASIN, 2026)
Although Fiqih instruction has long been implemented in schools, the learning process is still largely dominated by lecture-based methods and conventional media, resulting in low student motivation and suboptimal achievement of learning objectives. This study aimed to develop an interactive e-module using Flip PDF Professional based on QR Code technology and to evaluate its feasibility, effectiveness, and students’ responses to its use in Fiqih learning. The research employed a Research and Development (R&D) method with the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of two validators (a media expert and a content expert) and 30 eighth-grade students at MTsN 5 Jombang. The findings show that the developed e-module was categorized as highly feasible, with feasibility scores of 94% from the media expert and 86% from the content expert. Student responses were also very positive, with an average score of 89.3%, indicating that the e-module is engaging, easy to use, and supports students’ understanding of the Fiqih topics of sujud sahwi, tilawah, and syukur. The integration of QR Codes proved to enhance students’ access to videos, practice questions, and other supporting materials. These results confirm that the interactive e-module developed using Flip PDF Professional and QR Code technology is feasible and effective as a digital learning medium for Fiqih, aligned with the needs and characteristics of students in the digital era.